Back to School? Labor-Market Returns to Vocational Postsecondary Education - Petri Böckerman; Mika Haapanen; Christopher Jepsen (Institute for the Study of Labor (IZA), 2015)
Outside the U.S., little is known about the labor-market returns to vocational (or polytechnic) postsecondary education. This paper focuses on the labor-market returns to polytechnic bachelor's degrees in Finland. Using detailed administrative data, we estimate person fixed effect models to study returns for individuals with labor-force attachment prior to polytechnic school enrollment. We find sizable earnings and employment impacts for polytechnic bachelor's degrees, although the returns vary by personal characteristics and field of study.
Keywords: J24; I26; 330; vocational education; postsecondary education; labor-market returns